Highly Efficient Metasurface Quarter‐Wave Plate with Wave Front Engineering. Issue 3 (4th February 2021) - Chen, Chen; Gao, Shenglun; Xiao, Xingjian; Ye, Xin; Wu, Shengjie; Song, Wange; Li, Hanmeng; Zhu, Shining; Li, Tao
Abstract : Metasurfaces with local phase tuning by subwavelength elements promise unprecedented possibilities for ultrathin and multifunctional optical devices in which geometric phase design is widely used due to its resonant‐free and large tolerance in fabrications. By arranging the orientations of anisotropic nanoantennas, the geometric phase‐based metasurfaces can convert the incident spin light to its orthogonal state, and enable flexible wave front engineering together with the function of a half‐wave plate. Herein, by incorporating the propagation phase, another important optical device of quarter‐wave plate together with the wave front engineering as well, which is implemented by controlling both the cross‐ and copolarized light simultaneously with a singlet metasurface, is realized. Highly efficient conversion of the spin light to a variety of linearly polarized light is obtained for meta‐holograms, metalens focusing and imaging in the blue light region. This work provides a new strategy for efficient metasurfaces with both phase and polarization control, and enriches the functionalities of metasurface devices for wider application scenarios. Abstract : By controlling both the cross‐ and copolarized spin light simultaneously with the combination of the propagation phase and the geometric phase, the silicon nitride metasurface enables an efficient multifunction of quarter‐wave plate and wave front shaping, in the blue light region, which extends the common function of a half‐wave plate in spin light control by geometric phase designed metasurfaces.